ANALISIS BUTIR SOAL PENILAIAN AKHIR TAHUN MATA PELAJARAN BAHASA INDONESIA KELAS VIII SMPN 2 SUMBANG TAHUN PELAJARAN 2024/2025 - Apriliani, Apriliani; Memet Sudaryanto; Bivit Anggoro Prasetyo Nugroho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The assessment aims to demonstrate the level of competency mastery of students and the effectiveness of the learning methods applied by educators. Based on interviews conducted with Indonesian language teachers of eighth grade students at SMP Negeri 2 Sumbang, it was found that the level of student achievement of the minimum passing grade (KKM) in the Final Year Assessment was still relatively low. The quality of the questions greatly determines the effectiveness of assessing student competency. This study aims to analyze the quality of the final assessment questions for the Indonesian language subject for eighth grade students at SMP Negeri 2 Sumbang for the 2024/2025 academic year. This study used a quantitative approach with a descriptive method. The research object consisted of 45 PAT questions with a sample of 144 students. Data were obtained through documentation techniques and analyzed using a classical test theory approach assisted by the Anates application. The analysis focused on the aspects of validity, reliability, difficulty level, discriminating power, and effectiveness of distractors. The results showed that the quality of PAT items still varied and did not fully meet the criteria for a quality assessment instrument. Some items were not valid, the test reliability coefficient was low, the difficulty level distribution was not balanced, the discriminating power of some items was still weak, and most distractors did not function optimally.